Impacts of shelterbelt systems on pasture production and soil bacterial and fungal communities in agricultural fields - Thi Bao‐Anh Nguyen; Lina A. Henao; Zelin Li; Long Cheng; Hang‐Wei Hu (Journal of Sustainable Agriculture and Environment, 2023)
Abstract Introduction Shelterbelts, which provide protection for livestock and crops against severe weather conditions, have been recognised as important contributors to increased crop yields. Soil microorganisms play important roles in nutrient cycling, soil health and plant performance, thereby exerting significant influence on ecological services in terrestrial ecosystems. However, impacts of shelterbelts on soil microbial communities in pasture ecosystems remain poorly studied. Materials and Methods Here, we assessed the effect of shelterbelts (composed of Eucalyptus and native shrubs) on the pasture and nutrient productivity as well as soil bacterial and fungal communities at four distances from the shelterbelts with two different heights in two fields during spring and summer by applying amplicon sequencing, physicochemical and nutritional value analyses. Results The results showed that the shelterbelt height, distances from shelterbelts, seasons and their interactive effects substantially affected pasture yield, neutral detergent fibre, metabolisable energy and crude protein yields, but did not increase the pasture productivity in the rows adjacent to the shelterbelts. We also identified that the alpha diversity of bacteria and fungi did not significantly change across distances from the shelterbelts in both fields, but the community structure of soil bacteria and fungi was significantly influenced by distances from the shelterbelts. Interestingly, soil calcium (Ca) and shelterbelts were identified as top predictors of fungal community while soil pH and Ca was key drivers of bacterial community. Conclusion Our study provides novel knowledge in the impact of shelterbelts on pasture and nutritional production and soil microbial communities, which contributes to appropriate application and strategic management of the windbreak systems in agriculture production.